Implementation of Scaffolding Based on Audiovisual Media Through Television for Developing Students’ Arabic Listening Skills - Lubis, Arbonas; Rizkiansyah, Rikaz; Al Hafizh, Muhammad Abrar (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
The purpose of this study is to examine how scaffolding supported by audiovisual materials delivered through television contributes to the development of Arabic listening skills (mahārah al-istimā‘) among students at the intermediate level. The research is based on the premise that learners still experience difficulty processing spoken texts due to minimal exposure to proficiency-appropriate audio input and the absence of systematic instructional guidance during listening tasks. Using a qualitative descriptive approach, the study engaged Arabic teachers and students at a Ma’had At-Tibyan in Deli Serdang, North Sumatra, selected through purposive sampling. Data were gathered through classroom observations, interviews, and document analysis, then analyzed using the Miles and Huberman model, which includes data reduction, display, and the formulation of conclusions, and were strengthened by triangulation. The results show that scaffolding applied through modeling, prompting, guided practice, and gradual release significantly improved learners’ ability to identify sounds, understand core meanings, and connect information with relevant contexts. Television-based audiovisual media functioned effectively as a supportive tool because it is accessible, suited to students’ learning conditions, and does not rely on advanced technology. Students demonstrated clearer comprehension of global and specific information, as well as greater participation and confidence. The study highlights that combining scaffolding with structured audiovisual support via television offers a practical and adaptable alternative for schools with limited resources and enriches empirical insights into Arabic listening pedagogy.